تقييم الإنذار لداء هودجكن بعد المعالجة الكيماوية باستخدام الغاليوم المشع67 - شبيب حمزة (Latakia University Journal -Medical Sciences Series, 2013)
تم استقصاء 41 مريضاً بداء هودجكن بواسطة التصوير الومضاني بالغاليوم المشع 67 قبل وبعد المعالجة الكيماوية. خضع جميع المرضى في نفس الوقت للتصوير الطبقي المحوري. تم متابعة المرضى خلال 28-60 شهراً وبمتوسط 40 شهراً. قسم المرضى إلى مجموعتين بناء على إيجابية أو سلبية الفحص بالغاليوم المشع بعد المعالجة الكيماوية: كان الفحص سلبياً في 32 مريضاً و إيجابياً في تسعة مرضى. عاود أو انتكس المرض في 18،7% من المرضى السلبيي الفحص بالغاليوم وبقي منهم 93،8% أحياء حتى نهاية فترة المتابعة، بينما كانت نسبة معاودة أو انتكاس المرض 88،8% في المرضى الإيجابيي الفحص بالغاليوم، وبقي منهم 77،7 % أحياء حتى نهاية فترة المتابعة. كان هناك اختلاف إحصائي جوهري في معدل الحياة الإجمالي بين كلا المجموعتين (P=0.0041). لوحظ أيضاً تمايز إحصائي مهم بين المجموعتين من حيث الحياة الخالية من المرض (P<0.001). كان الخطر النسبي للموت في مجموعة مرضى الغاليوم الإيجابي 4،3 ضعفاً عما هي عليه في أولئك السلبيي الفحص بالغاليوم، بينما ازداد الخطر النسبي من النكس في مجموعة مرضى الغاليوم الإيجابيي إلى 12 ضعفاً عما هي عليه في مجموعة المرضى السلبيي الفحص بالغاليوم. كانت القيمة المتوقعة الإيجابية والسلبية لمعاودة المرض هي 89% و 81% على التوالي. Forty one patients with Hodgkin’s disease (HD) were investigated with 67Ga Scintigraphy before and after the completion of chemotherapy. At the same time, all patients underwent computer tomography (CT) scans. Patients were followed up for 28-60 months (average 40 months). Patients were divided into groups according to the positivity or negativity of the gallium scan after chemotherapy: 32 patients had negative gallium scans, and 9 patients had positive gallium scans. In the gallium–negative group, 18.7% of the patients relapsed and 93.8% were alive at the end of the follow-up. In the gallium positive-group, 88.8% of the patients had recurrent disease and 77.7% were alive after intensive chemotherapy. There was a statistically significant difference in the overall survival between patients with positive gallium results and patients with negative gallium results (P= 0.0041). The disease-free survival differed significantly between patients with positive gallium scan and patients with negative gallium scan at the end of chemotherapy (P< 0.001). The relative risk of death was 4.3 and the relative risk of relapse was 12 for patients with positive gallium scans, in comparison to those with negative gallium scans. The positive and negative predictive value for predicting relapse was 89% and 81% respectively.